Tumor‐Associated Protrusion Fluctuations as a Signature of Cancer Invasiveness. Issue 9 (3rd July 2021) - Caballero, David; Brancato, Virginia; Lima, Ana C.; Abreu, Catarina M.; Neves, Nuno M.; Correlo, Vitor M.; Oliveira, Joaquim M.; Reis, Rui L.; Kundu, Subhas C.
Abstract: The generation of invasive fluctuating protrusions is a distinctive feature of tumor dissemination. During the invasion, individual cancer cells modulate the morphodynamics of protrusions to optimize their migration efficiency. However, it remains unclear how protrusion fluctuations govern the invasion of more complex multi‐cellular structures, such as tumors, and their correlation with the tumor metastatic potential. Herein, a reductionist approach based on 3D tumor cell micro‐spheroids with different invasion capabilities is used as a model to decipher the role of tumor‐associated fluctuating protrusions in cancer progression. To quantify fluctuations, a set of key biophysical parameters that precisely correlate with the invasive potential of tumors is defined. It is shown that different pharmacological drugs and cytokines are capable of modulating protrusion activity, significantly altering protrusion fluctuations, and tumor invasiveness. This correlation is used to define a novel quantitative invasion index encoding the key biophysical parameters of fluctuations and the relative levels of cell‐cell/matrix interactions, which is capable of assessing the tumor's metastatic capability solely based on its magnitude. Overall, this study provides new insights into how protrusion fluctuations regulate tumor cell invasion, suggesting that they may be employed as a novel early indicator, or biophysical signature, of the metastatic potential of tumors. Abstract : The capability of tumor‐associated protrusion fluctuations to assess the invasion potential of tumors is explored. With this aim, a new set of quantitative parameters is defined as the biophysical signature of tumors. Protrusion fluctuations are proposed as a novel morphodynamic indicator of invasion, a needed active precursor of tumor spreading, and a key prognostic marker for tumor invasiveness.